(untitled) (Research, Society and Development, 2019)
This article aims to analyze the social actors involved in the media coverage of the 2019 measles coverage in Brazil. This is a qualitative study based on documentary research. Fifty news, results from searches for ’measles’ and ’measles and autism’ in the Google News search engine, were evaluated. News search was conducted in august 2019. Almost exclusive predilection was noted by official sources and biomedical authorities. Few independent sources have been heard. The vehicles gave preference to monophonic discourse, even when they proposed to debate with different actors. Little recourse was made to ordinary citizens and individuals. It is concluded that the media, a strong influencer of popular opinion and health policies, has little explored the diversity of social actors and, consequently, their experiences and perspectives.